STUDIES ON MORPHOMETRIC ANALYSIS OF PILA GLOBOSA (SWAINSON, 1822) FROM MANIKA OXBOW LAKE, MUZAFFARPUR, BIHAR - PRASAD, DIKESHWAR; NAYAK, S. K.; MOGLEKAR, H. S.; KUMAR, SHIVENDRA; SINGH, M. K.; BRAHMCHARY, R. K.; KUMAR, ANIRUDH; Srivastava, P. P. (Journal of the Inland Fisheries Society of India, 2026)
The research took place at Manika Oxbow Lake in Bihar’s Muzaffarpur district, situated at latitude 26.094027 and longitude 85.445778 with an accuracy of 1900.0 m. Two stations were chosen based on water availability, and P. globosa samples were collected fortnightly over twelve months (September 2021 to August 2022) using random sampling by local fishermen and women. Around 720 P. globosa individuals were collected and morphometrically analyzed during the study period. The mean values of biometric characters of P. globosa like Total Shell Length (TSL) was 4.8±0.5, Total Shell Width (TSW) was 4.9±0.5, Spire length (SPL) was 2.0±0.2, Spire Height (SPH) was 3.9±0.5, Spire Width (SPW) was 3.5±0.4, Base Length (BL) was 4.1±0.5, Aperture Length (AL) was 3.5±0.4, Aperture Width (AW) was 2.2±0.2, Aperture Thickness (AT) was 0.28±0.03, Shell Thickness (ST) was 0.20±0.03 in cm, Shell Wet Weight (SWW) was 35.9±11.1 and Shell Dry Weight (SDW) was 9.0±3.0 in gm. The regression between TSL/TSW (TSL=0.9975+0.0174 TSW), TSL/SPL (TSL=1.0146-0.3964 SPL), TSL/BL (TSL=0.8039+0.0681 BL), TSL/AL (TSL=0.9334-0.0859 AL), TSL/AW (TSL=0.8627- 0.2518 AW), TSL/SPH (TSL = 0.9884-0.0762 SPH), TSL/SPW (TSL=0.9778-0.1193 SPW), TSL/AT (TSL=0.2499-0.7174 AT), TSL/ST (TSL=0.2665-0.8898 ST) and TSL/SWW (TSL=1.96+0.2076 SWW). The negative allometric growth indicated an unhealthy P. globosa population in Manika Oxbow Lake. The estimated Catch, CPUE, and MSY suggested overexploitation of the P. globosa stock in the lake.